Analytical modeling of grinding wheel loading phenomena - Adibi, H.; Rezaei, S.M.; Sarhan, Ahmed A.D. (2013)
Wheel surface condition plays an important role in the grinding operation. Grinding wheel loading, meaning chip accumulation in the space between grains, leads to deteriorating wheel cutting ability and causes excessive force and temperature. This paper presents an analytical model of wheel loading phenomena as a function of cutting parameters, wheel structure, and material properties. The model is based on the adhesion of workpiece material to abrasive grain surface. It is validated by experimental results from grinding nickel-based superalloy with cubic boron nitride vitrified wheel. This model considers wheel specifications including abrasive grains size and the number of cutting edges. Cutting parameters and process temperature are the other determinant factors. On the basis of this model and empirical results, the effects of the various process parameters are presented.